Kurâ Xunâry memória do povo Kurâ Bakairi - Xagope, Valdo Kutaiava (2018)
In the specific case of this research, the analyst is both a researcher and Kurâ Bakairi. So the look is different. We have as objectives the record of much of the Kurâ Bakairi society and the discussion of how millennial knowledge has been kept and re-signified within a specific materiality - orality. How are these knowledge archived? How, despite the pressing confrontation between the Bakairi world and the Karaiwa world, do the Kurâs recognize and recognize themselves in the historical fabric of beliefs, cultural gestures, moral principles and social organization, understood as traces of the basic structure of Kurâ identity? The work is divided into three parts. A theoretical, based on the concepts of researchers who carried out research on the Kurâ and focus, above all, the contribution of Karl von den Steinen in the books Central Brazil: expedition of 1884 for exploration of the Xingu River and Between aborigines of central Brazil. We sought to establish a relationship between the Xingu Bakairi and the Bakairi of Rio Novo, and I also observe the impasse created by the presence of a third group of Bakairi. From this information, we try to understand how the process of meeting different Baikairi groups was conducted in two current locations: PI Simões Lopes and PI Santana. The second part of the paper describes the social organization Kurâ; for that, I use the work of Taukane (1996), who investigates the traditional education of the Kurâs, observing the changes that have occurred throughout time in all directions; also we record the importance of the pyaji (pajé) among the Kurâ, since these people believe in the existence of two types of disease (Kurâ and Karaiwa). Its whole event is focused on the spirituality of this people, the importance of being human as a person, so that life has great importance for this culture. For this people, all passages in the life cycle have markers of time: birth, puberty, adulthood and death are reported in the essence of Kurâ, which is being lost. The third part of the work is about the Kurâ mythology and the Kurâ memory works. I base my observations mainly on Discourse and Orality: a study in the indigenous language (SOUZA, 1994, among others). In this work, I always call the Bakairi of Kurâ, for Bakairi is a word that has no meaning within the Kurâ ethnicity.